High speed end-to-end connection management in a bridged IEEE 1394 network of professional audio devices - Okai-Tettey, Harold A (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
A number of companies have developed a variety of network approaches to the transfer of audio and MIDI data. By doing this, they have addressed the configuration complications that were present when using direct patching for analogue audio, digital audio, word clock, and control connections. Along with their approaches, controlling software, usually running on a PC, is used to set up and manage audio routings from the outputs to the inputs of devices. However one of the advantages of direct patching is the conceptual simplicity it provides for a user in connecting plugs of devices, the ability to connect from the host plug of one device to the host plug of another. The connection management or routing applications of the current audio networks do not allow for such a capability, and instead employ what is referred to as a two-step approach to connection management. This two-step approach requires that devices be first configured at the transport layer of the network for input and output routings, after which the transmit and receive plugs of devices are manually configured to transmit or receive data. From a user's point of view, it is desirable for the connection management or audio routing applications of the current audio networks to be able to establish routings directly between the host plugs of devices, and not the audio channels exposed by a network's transport, as is currently the case. The main goal of this work has been to retain the conceptual simplicity of point-to-point connection management within digital audio networks, while gaining all the benefits that digital audio networking can offer.
Keywords: IEEE 1394 (Standard); Digital communications; Computer networks; Sound -- Recording and reproducing -- Digital techniques; Computer sound processing